A SWOT (Strength Weakness Opportunity and Threat) Analysis as a Strategy to Enhance Competitiveness - Moh Mardiyana; M Ihsan; Adrial Adrial; Hufrizatul Parida; Syahril Sidiq; Taufik Hidayat (Sultan Publisher, 2022)
This study aims to determine how an analysis of Strengths, weaknesses, and opportunities, and threat is used as a strategy to increase competitiveness and its obstacles in Denpasar Sharia Rural Banks. The research method used was a quantitative approach in the form of case studies descriptive. The SWOT analysis used is the analytical method descriptive, SWOT Matrix, and SWOT diagram analysis. Data collection techniques in this study are interviews and literature. The results showed that the SWOT analysis as a strategy to increase competitiveness needs to be re-evaluated, so that good performance is formed from within and from outside the organization.